PERLINDUNGAN DEBITUR PADA LAYANAN PINJAMAN UANG BERBASIS FINANCIAL TECHNOLOGY - Ria Agustianti (Jurnal Ilmiah Dinamika Hukum, 2020)
Technology assistance is very helpful for community activities including financial institutions, such as the application of Fintech (Financial Technology). Fintech utilizes technology to improve banking and financial services performed by companies by utilizing software technology. Along with the development, Fintech began to have a negative impact, especially from the money loan service or Fintech Peer to Peer Lending (P2PL). the problem is how is the protection for debtors / customers, such as attempts to intimidate customers who have difficulty paying. The method used in this research is normative juridical, namely research based on secondary data, which is then analyzed qualitatively and presented in a qualitative form.Based on the research results, it can be concluded that protection for debtors or customers who feel disadvantaged can take 5 (five) ways, which are regulated in the Consumer Protection Law, OJK Regulation, ITE Law, BI and Government Regulations. Safeguards in the Consumer Protection Law are accommodated in Article 4. OJK's efforts, in collaboration with Kominfo and AFPI, are that if there is intimidation that is detrimental to the debtor, the debtor can submit a complaint report through the website page provided by the OJK and AFPI. Debtors can also report to the authorities. The ITE Law can be seen in Article 26 of the ITE Law. Efforts made by Bank Indonesia, namely BI to form the Bank Indonesia Fintech Office (BI-FTO) and recommend to follow the existing regulations in PBI No. 16/8 / PBI / 2014 and PBI No 18/17 / PBI / 2016 concerning Electronic Money (PBI E-Money). Keywords: Financial Technology, Legal Protection, Debtor Efforts